(untitled) (International Journal of Innovative Technologies in Economy, 2021)
There is an urgent need for a comprehensive study and analysis of negative processes of deepening the level of second relations in the economy. The ghost economy is the result of the functioning and increasing signs of a systemic crisis in the economy, which arises due to the discrepancy and inadequacy of the methods used to implement market transformations. The spread of the gray economy occurred on the basis of the destruction of existing distribution relations and the construction of new ones, which significantly violated the established balance of economic entities interests, the parity of its separate spheres development, and the motivation for effective management. Another meaningful aspect is that the gray sector of the economy in any country really exists; it quickly reacts to changes in the implementation of the state economic life. That is why it is extremely important when studying the problem of increasing the scale of the gray economy is the prompt and rapid accumulation of information dealing with changes in its basic indicators. Hiding of tax revenues is a crime, and tax minimization, that is, an attempt to reduce their amount, is completely legal and provides the work of a large number of specialists in the field of tax law and accounting. But on the other hand, for economic entities operating in Ukraine, the critical threat is not the fiscal capability, but the uncertainty in the legislation and the political and economic life of the country.